Impact of layer rotation on micro-structure, grain size, surface integrity and mechanical behaviour of SLM Al-Si-10Mg alloy - Munish Kumar Gupta (Journal of Materials Research and Technology, 2020)
Selective laser melting (SLM) is one of the appreciable technologies that is directly used to manufacture the intricate and highly accurate parts within short period of time. However, the involvement of various parameters in SLM process is gaining more and more attention of the scientific community. In this work, the research efforts have been made to emphasize on the effects of one of the prominent parameters of SLM process i.e., layer rotation on the microstructure, grain size, surface topography, residual stresses and mechanical behaviour of selective laser melted Al-Si-10Mg alloy. The standard benchmark components were fabricated by varying the layer rotation values at three different angles i.e., 0°, 45° and 90°. The result of microstructural analysis (using EBSD, SEM and XRD) revealed that the Al-Si-10Mg produced the cellular structure having less pores and defects at 90-degree layer rotation angle. The grain size, residual stresses and surface roughness (77.02%) values were also reduced with increase in layer rotation angle values. Furthermore, the micro-hardness (upto 19.6 %), tensile strength, %elongation (87.29 %) and relative density values were significantly enhanced at higher angle of layer rotations mainly due to the reduction in porosity and better interlayer metallurgical bonding.